Outcomes in older patients with biliary tract cancer. (March 2021) - McNamara, Mairéad G.; de Liguori Carino, Nicola; Kapacee, Zainul Abedin; Lamarca, Angela; Valle, Juan W.
Abstract: The majority of patients diagnosed with cancer are ≥65 years. However, inclusion of older patients with cancer in clinical trials is limited, and so there is less evidence to guide systemic therapeutic decisions in these patients. There is also debate surrounding the definition of "older patients". Additionally, comorbidities, as well as life expectancy will influence compliance to any treatment, and physicians may favour less intense regimens for these patients or best supportive care alone. In patients with biliary tract cancer (BTC), surgery followed by adjuvant capecitabine (BILCAP phase 3 trial) is the only potentially curative option, but patients often present with advanced disease, and palliative systemic treatment is given. The availability of novel targeted therapies (oral and monotherapy) in selected populations of patients with BTC may increase the therapeutic artillery for these older patients. Trials to date in patients with BTC have not been age-specific and have not always included age subgroup analysis, and so the evidence to support treatment of older patients is derived via extrapolation, primarily, with only 35% being >60 years in the adjuvant BILCAP study, for example. When this evidence is provided, treated patients tend to gain equivalent survival benefit, irrespective of age. A comprehensive clinical geriatric assessment is recommended. Revision of existing BTC treatment guidelines should incorporate some reference to best practice in older patients with BTC. Observational data may also provide valuable insights in this population. Age sub-group analysis should be encouraged in prospective clinical trials including patients with BTC, with age-specific trials favoured. Highlights: Trials in BTC have not been age-specific nor always included age subgroup analysis. Observational data may provide valuable insights in this population. Retrospective evidence reports equivalent survival benefit, irrespective of age. Comprehensive clinical geriatric assessments are recommended. BTC therapy guidelines should reference best practice in older patients with BTC.